Quantitative mass spectrometry analysis of the injured proximal and distal human digital nerve ends - Frostadottir, Drifa; Welinder, Charlotte; Perez, Raquel; Dahlin, Lars B. (Frontiers in Molecular Neuroscience, 2024)
IntroductionProteomic analysis of injured human peripheral nerves, particularly focusing on events occurring in the proximal and distal nerve ends, remains relatively underexplored. This study aimed to investigate the molecular patterns underlying a digital nerve injury, focusing on differences in protein expression between the proximal and distal nerve ends.MethodsA total of 26 human injured digital nerve samples (24 men; 2 women; median age 47 [30–66] years), harvested during primary nerve repair within 48 h post-injury from proximal and distal nerve ends, were analyzed using mass spectrometry.ResultsA total of 3,914 proteins were identified, with 127 proteins showing significant differences in abundance between the proximal and the distal nerve ends. The downregulation of proteins in the distal nerve end was associated with synaptic transmission, autophagy, neurotransmitter regulation, cell adhesion and migration. Conversely, proteins upregulated in the distal nerve end were implicated in cellular stress response, neuromuscular junction stability and muscle contraction, neuronal excitability and neurotransmitter release, synaptic vesicle recycling and axon guidance and angiogenesis.DiscussionInvestigation of proteins, with functional annotations analysis, in proximal and the distal ends of human injured digital nerves, revealed dynamic cellular responses aimed at promoting tissue degeneration and restoration, while suppressing non-essential processes.